2020
DOI: 10.1002/ajmg.a.61631
|View full text |Cite
|
Sign up to set email alerts
|

Parent perceptions, beliefs, and fears around genetic treatments and cures for children with Angelman syndrome

Abstract: Genetic therapies have shown recent promise in alleviating some of the cognitive issues associated with some genetic disorders; however, these therapies may come with significant health and socio-ethical concerns, particularly when they involve child participants. Little is known about what parents of children with genetic disorders think about genetic therapies, or about their knowledge of how genetic-based therapy might treat their child's symptoms. Forty-two parents of children with Angelman syndrome (AS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Developmental studies indicate that children with AS caused by a deletion are developmentally more delayed across all domains compared with those due to a UBE3A pathogenic variant or UPD [ 14 , 54 , 60 ]. Cognitive skills are much lower in the deletion group than in the non-deletion group [ 14 , 60 ]. Delayed gross and fine motor skills are more severe in the deletion group [ 14 , 53 , 60 , 61 , 62 ].…”
Section: Genotype–phenotype Correlation In Angelman Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Developmental studies indicate that children with AS caused by a deletion are developmentally more delayed across all domains compared with those due to a UBE3A pathogenic variant or UPD [ 14 , 54 , 60 ]. Cognitive skills are much lower in the deletion group than in the non-deletion group [ 14 , 60 ]. Delayed gross and fine motor skills are more severe in the deletion group [ 14 , 53 , 60 , 61 , 62 ].…”
Section: Genotype–phenotype Correlation In Angelman Syndromementioning
confidence: 99%
“…Cognitive skills are much lower in the deletion group than in the non-deletion group [ 14 , 60 ]. Delayed gross and fine motor skills are more severe in the deletion group [ 14 , 53 , 60 , 61 , 62 ]. Seizure and microcephaly have been reported to be more common and severe in the deletion group [ 53 , 63 , 64 , 65 ].…”
Section: Genotype–phenotype Correlation In Angelman Syndromementioning
confidence: 99%
“…Parents of children with Angelman syndrome, a genetic disorder causing severe intellectual and physical disability, overwhelmingly identified cure as a research priority. 13 By contrast, a survey of parents of children with Down syndrome found that while 61% favoured treatment that would reduce symptoms, only 41% supported a curative approach. 14 Parents of children with…”
Section: Discussionmentioning
confidence: 97%
“…Parental views about gene therapy for life‐threatening genetic disorders are influenced by the severity of the condition and available treatment. Parents of children with Angelman syndrome, a genetic disorder causing severe intellectual and physical disability, overwhelmingly identified cure as a research priority 13 . By contrast, a survey of parents of children with Down syndrome found that while 61% favoured treatment that would reduce symptoms, only 41% supported a curative approach 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The decision to enroll a child into a clinical trial requires serious deliberation from consenting parents and guardians; these are weighty decisions that can impact their child's health, well-being, and the well-being of their family-and the potential promise of an otherwise unobtainable disease-modifying therapy may have an unintended coercive appeal. Moreover, the depth of understanding of genetic disease, inheritance, genetic therapies, and research trials is highly variable across parents with children with a variety of genetic syndromes [75]. It is critical that for such trials, the purpose, procedures, and expected outcomes be clearly discussed and explained.…”
Section: Safety and Ethical Considerationsmentioning
confidence: 99%